Materialność ruchomego języka - Orska, Joanna (Zagadnienia Rodzajów Literackich, 2019)
In this paper I reassess Adam Wazyk’s meta-poetical statements of the late 1960s and 1970s as also being a time of recovery for crucial avant-garde conceptions in Poland. The artist starting his poetic career as a member of “Nowa Sztuka” (“New Art”) avant-garde group around the 1920s, didn’t abandon his early intuitions on art after World War II. These in turn can be bound to his life-interests in French avant-garde poetry and in French surrealism. By indicating the poetic affinities of these art strategies, I attempt to highlight similar sources of surrealistic experiments in poetry in France and in pre-war Poland. In this particular case this brings us to avant-garde film techniques, seen through the prism of Deleuze’s dissertation on “Cinema”, especially in relation to his remarks on the early silent-movies. The notion of ‘movement-image’, created in the wake of Bergsonian philosophy in relation to time and movement in modernity, occurs as helpful in that matter. The core of my argument connects to the phenomenon of materiality often associated with surrealist practices, invoking here questions of a quite specific kind, that is questions about the matter of language and the matter of poesies.